Perancangan Sistem Informasi Website Donasi - Arif Marjuki; Haryanto Haryanto; Dedy Iskandar; Andri Cahyo Purnomo; Arif Novrizal (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study designs and implements a web-based digital donation information system to strengthen transparency and public reporting for PMI Kota Tangerang. The system was developed through an empirical software engineering approach grounded in direct organizational observation, enabling the requirements to reflect real donation management practices, administrative constraints, and public accountability needs. The proposed platform integrates public information dissemination, online donation workflows, automated transaction recording, and reporting features within a unified architecture. The public-facing interface enhances accessibility to organizational updates and donation programs, supporting donors’ trust formation through consistent institutional identity and clear information structure. On the operational side, an administrative dashboard provides centralized control over donation data, transaction status management, and structured records to support timely and verifiable reporting. Functional validation was conducted using black-box testing to ensure that core modules operate correctly across defined user scenarios, including donation submission, data storage, report generation, and role-based access. The results indicate that the system is technically feasible and organizationally relevant, offering a scalable digital mechanism to reduce reporting inconsistencies and improve public confidence in humanitarian fundraising.